ANALISA KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK DIBIDANG KESEHATAN: (Studi Kasus Puskesmas Babelan 1) - Fani Sahabi'ah; Bilqis Anas Thalib; Ersa Falena Fitri; Zaeicha Putri Rahmawanti (LPPM Universitas Abdurrab, 2025)
Health services are a form of public service which is an activity or series of activities in order to fulfill service needs in accordance with statutory regulations for every citizen provided by public service providers established based on law for public service activities. The aim of conducting research at Babelan 1 Community Health Center is to determine the standard of health services available at Babelan 1 Community Health Center, so that services to the community can run optimally and the level of public health can increase. In this research, the researcher used a descriptive research method with a qualitative approach and used data collection techniques through interviews and documentation carried out at the Babelan Community Health Center 1. The results of the research showed that the quality of public services greatly influences community satisfaction, the researcher emphasized aspects: tangible, empathy, reliability, responsiveness and assurance to analyze public satisfaction with public services.